THE PROBLEM OF INTERCHANGEABILITY IN SYNONYMS OF MODERN ENGLISH - Alimova Kamola (Scholars Digest Publishing, 2024)
In this article, the author considers such an important problem for the synonymy of modern English as interchangeability. The characteristic stylistic features of synonyms, their extensive classification, scope of application, boundaries of the synonymous series, reasons for errors in use and the results of synonymous substitutions are analyzed. The dependence of interchangeability on the source of the word is revealed.
Keywords: synonyms, connotation, synonymic dominant, euphemisms, interchangeability, English language, classification.